The Role of Galactose-induced Oxidative Stress on Cellular Aging: A Literature Review - Putri Krishna Kumara Dewi; Ni Made Dwi Rosmiati; Citra Ariani (Faculty of Medicine, Universitas Mataram, 2026)
Aging is a complex process impacted by both internal and external causes. Nutrition is a crucial extrinsic factor in the development of aging and degenerative disorders. D-galactose is involved in many aging mechanisms in the brain, heart, liver, kidney, and skin. Galactose-induced cellular aging is primarily caused by oxidative stress and a reduced antioxidant system. Overproduction of ROS can damage proteins, lipids, and DNA. The recommended daily dietary limit for D-galactose is 50 grams for healthy people who can completely remove it within 8 hours. An in vivo study revealed that consuming 150 mg/kg/day of galactose led to metabolic issues, heightened blood pressure, and disrupted cardiac sympathovagal balance. These outcomes resulted from compromised cardiac mitochondrial activity, elevated oxidative stress, inflammation, and mitochondrial dysfunction, which caused cell death and eventually cardiac failure. A diet high in carbohydrates, particularly those derived from dairy products and their derivatives, can lead to the accumulation of galactose and its metabolites within cells. This buildup subsequently increases reactive oxygen species and reduces antioxidant capacity, resulting in mitochondrial dysfunction and heightened oxidative and osmotic stress. The culmination of these processes is a decline in cellular function, senescence, and accelerated organ aging.